The Function and The Role of Public Relation in The Milenial Education Center - Hidayat, Taufik (International Conference of Moslem Society, 2019)
The development of an educational institution is influenced by two factors, they are internal and external factors. The internal factor becomes the mainly attention as the first step to develop the institution to be more accountable institution and an idol in the public. one of the forgotten and neglected roles is its role as a public relation. One of the indicators of a successful public relation is the interest of the public to enter the institution. Otherwise, the unsuccessful public relation in the institution is that the public has the doubt, pessimism about the institution, which can decrease public interest and trust to the institution, and can cause the institution to come into bankrupcy. Developing the understanding about the vision and mission in an institution/school is an important part in public relation. It is necessary for the public to get some information easily and hoe the institution can raise public curiosity about the institution sp that they . they will follows the aim of the institution. Furthermore, in this milleneal era, in which the development of technology is widely spread, the information is easily accessible so that the public relation has a wider role to give the data or information efficiently and effectively. In addition, a public relation has to fulfill the function of the public relation and the management. They are the function as a research planning, coordinating, participation and advisory. The activity of the public relation is the researching facts or fact finding, planning, communication or evaluating. Finally, the public relation has to reflect to become a mutual way of relationship, and it can also build a good relation between two profitable sides and giving feedback to the institution or the public.